Essentialism affects the perceived compatibility of minority culture maintenance and majority culture adoption preferences. (27th September 2020) - Moftizadeh, Nali; Zagefka, Hanna; Mohamed, Abdinasir
Abstract : This paper presents two cross‐sectional survey studies, both conducted in Britain, which focus on how different cultural identities are managed in multicultural settings. Specifically, the studies explored the extent to which essentialism moderates the perceived compatibility of acculturation orientations, heritage culture maintenance and majority culture adoption. In study 1, participants ( N  = 198) were Somali minority members living in the UK. It was found when minority members essentialized Britishness themselves, and when they perceived that British people essentialized Britishness, they saw a desire to maintain the culture of origin and a desire adopt the majority culture as conflicting with each other. In study 2, participants ( N  = 200) were white British majority members living in the UK. Findings showed that when white British majority members essentialized Britishness, they too perceived the two acculturation preferences as being incompatible with each other. Taken together, these studies show that essentializing British identity can lead to a view that the majority and minority cultures are mutually exclusive. Implications for intergroup relations and integration into British society are discussed.